CLINICAL APPROACHES TO TEACHING SELF MONITORING STRATEGIES FOR PATIENTS WITH HEART FAILURE - Boymurodova N. Ch. (Modern American Journals, 2025)
Heart Failure (HF) is a major challenge in global healthcare, characterized by high morbidity and mortality rates. Effective management of this condition depends not only on adequate medical treatment provided by physicians but also on the patient’s ability to engage in self-monitoring. Research indicates that patients who develop self-monitoring skills have a reduced risk of disease progression to severe stages, a lower likelihood of hospitalization, and an overall improvement in both quality and longevity of life. This article explores the clinical and technological aspects of educating HF patients in self-monitoring, highlighting advanced educational strategies, telemedicine solutions, and the potential of artificial intelligence. Additionally, international protocols, pharmacological treatment options, and recommendations for actively involving patients in disease monitoring are analyzed.
Keywords: Heart failure, self-monitoring, patient training, cardiovascular diseases, telemedicine, artificial intelligence, clinical recommendations.